ロイコトリエンB4は分泌型ホスホリパーゼA2によるアポトーシスに関与しているのか - 矢上, 達郎; 山本, 泰弘 (日本薬理学会年会要旨集, 2023)
Neurological diseases e.g. brain ischemia are associated with secretory phospholipase A2 (sPLA2). The group IB sPLA2 (sPLA2-IB) induced neuronal cell death via apoptosis, which were accompanied with chromatin condensation and DNA fragmentation. Previously, we had established the sPLA2-IB-induced neuronal apoptosis as the in vitro model for cerebral ischemia. We reported that lipoxygenase inhibitors prevented neurons from the toxicity of sPLA2-IB, suggesting an involvement of LTs to the neurotoxicity of sPLA2-IB. Furthermore, leukotriene (LT) receptor blockers prevented neurons from the sPLA2-IB-condensed chromatin and fragmented DNA, suggesting an involvement of LTs in the sPLA2-IB-induced neuronal apoptosis. In the present study, we ascertained whether LTs were involved in the sPLA2-IB-induced neuronal apoptosis. Prior to neuronal apoptosis, sPLA2-IB generated LTB4 in the primary culture of rat cortical neurons. The sPLA2-IB-generated-LTB4 was reduced vitamin E (radical scavenger) and nimodipine (L-voltage-dependent calcium channel blocker). Since reactive oxygen species (ROS) and calcium influx via L-VDCC were located at the up-streams of sPLA2-IB-induced neuronal apoptosis, LTB4 was located in its down-stream. However, the neurotoxicity of LTB4 was not detected. In addition, we could detect no neurotoxicity of LTC4, LTD4 or LTE4. Further studies are required to clarify how LT receptor blockers prevented neurons from the sPLA2-IB-induced apoptosis.